Pengaruh Bystander Effect, Whistleblowing dan Locus of Control Terhadap Kecurangan Akuntansi dengan Love of Money sebagai Variabel Moderasi - Alia Surya Ningrum; Suwandi Suwandi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of the bystander effect, whistleblowing and locus of control on accounting fraud with love of money as a moderation variable. The data collection method was carried out using a questionnaire. The research subjects were employees of the Gresik Regency Regional Apparatus Organization (OPD). The total sample processed was 100. The data in this research was obtained using PLS-SEM. The result of this research show that the bystander effect and whistleblowing variables have a positive and significant effect on accounting fraud, while locus of control has a negative and significant effect on accounting fraud. The love of money variable moderates the influence of bystander effects on accounting fraud, but love of moneuy variabel does not moderate the influence of whistleblowing and locus of control on accounting fraud.